Assessing Translation Quality of the Indonesian Translation of Barack Obama’s Speech in 2012 United Nations General Assembly - Suwarni Wijaya Halim (Universitas Bunda Mulia, 2017)
This research aims to assess the translation quality by comparing the source text and the target text. The researcher decided to compare the speech by Barack Obama in 2012 United Nations General Assembly and its translation in Indonesian. The model that the researcher used to find out the translation quality is Translation Quality Assessment: A Model Revisited by Juliane House. The model focuses on comparing both source and target text in order to acquire some mismatches and errors before concluding the statement of quality. In the end, the researcher got the conclusion that the interpersonal function is slightly changed while the ideational function remains the same. Moreover, the researcher also concluded that this model is more appropriate to be used in assessing the translation quality of explicit texts such as texts with informative and operative purposes.Keywords: translation quality assessment, speech, juliane house, mismatches, errors